Mental Models Based on Students Thinking Style About Objects in Static Fluid - Gustina; Jusman Mansyur; Wahyuni N Laratu; Rahmat Tule (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to describe a mental models based on students' thinking styles about objects in static fluids. The type of research used is quasi-qualitative with a research design using Simple Research Design (SRD). This research was carried out at MAN Insan Cendikia, Palu City for grade XII students in the 2023 academic year, with 30 students as subjects. The instruments of this research are questionnaires, two-level test and interview guide. The data analysis technique used is the "Miles and Huberman Model" namely data reduction, data modeling and drawing conclusions. The results of data analysis showed that out of 30 students, there were 8 students with a Concrete sequential (Cs) thinking style, 12 students with an Abstract sequential (As) thinking style, 6 students with a Concrete random (Cr) thinking style, and 4 students with a Abstract random (Ar) thinking style. The group tested with abstract problem tended to have a higher average score than the group tested with concrete problem. When given abstract ploblem the Abstract sequential (As) and Sequential concrete (Cs) groups had a higher average score than the Abstract random (Ar) and Concrete random (Cr) groups.